2009
DOI: 10.1016/j.molcel.2009.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Ligase Nedd4L Targets Activated Smad2/3 to Limit TGF-β Signaling

Abstract: Summary TGFβ induces phosphorylation of the transcription factors Smad2 and Smad3 at the C-terminus as well as at an interdomain linker region. TGFβ-induced linker phosphorylation marks the activated Smad proteins for proteasome-mediated destruction. Here we identify Nedd4L as the ubiquitin ligase responsible for this step. Through its WW domain Nedd4L specifically recognizes a TGFβ-induced phosphoThr-ProTyr motif in the linker region, resulting in Smad2/3 poly-ubiquitination and degradation. Nedd4L is not int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
345
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(373 citation statements)
references
References 43 publications
17
345
4
1
Order By: Relevance
“…Diseased valves have been shown previously to express the pleiotropic growth factor, TGF-β1 [32,30,45] and a mouse model of CAVD has demonstrated elevated levels of phosphorylated Smad transcription factors in aortic valves [46]. This study demonstrates that in human aortic valve lesions expression of both TGFβ1 and phosphorylated Smad2/3 are elevated throughout the thickened valve leaflets.…”
Section: Discussionsupporting
confidence: 50%
“…Diseased valves have been shown previously to express the pleiotropic growth factor, TGF-β1 [32,30,45] and a mouse model of CAVD has demonstrated elevated levels of phosphorylated Smad transcription factors in aortic valves [46]. This study demonstrates that in human aortic valve lesions expression of both TGFβ1 and phosphorylated Smad2/3 are elevated throughout the thickened valve leaflets.…”
Section: Discussionsupporting
confidence: 50%
“…In the larval wing disk, this occurs in vein precursor cells and results in the ectopic veins of MGM and DN-Zw3 wings as well as the loss of veins in CA-Zw3 and MadRNAi wings. This aspect of the Zw3-Mad interaction is consistent with prior studies and is further supported by Gao et al (2009). On the basis of studies in mammalian cells, they identified Nedd4L and Smurf1 as ubiquitin ligases recognizing doubly phosphorylated (Receptor and Gsk3-b) Smad2/3 or Smad1, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…The linker domain undergoes regulatory phosphorylation by mitogen-activated protein kinase (MAPK) pathways including extracellular signal-regulated kinase, c-Jun N-terminal kinase (JNK), p38 MAPK, and cyclin-dependent kinase (CDK) as well as glycogen synthase kinase 3-b (Fig. 1a, middle) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%